2012
DOI: 10.1007/s40003-011-0003-5
|View full text |Cite
|
Sign up to set email alerts
|

Rice Blast Management Through Host-Plant Resistance: Retrospect and Prospects

Abstract: Rice (Oryza sativa) plays a significant role in achieving global food security. However, it suffers from several biotic and abiotic stresses that seriously affect its production. Rice blast caused by hemibiotropic fungal pathogen Magnaporthe oryzae is one of the most widespread and devastating diseases of rice. The crop rice is vulnerable to this pathogen from seedlings to adult plant stages affecting leaves, nodes, collar, panicles and roots. This disease can be effectively managed through host resistance. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
181
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(201 citation statements)
references
References 113 publications
4
181
0
8
Order By: Relevance
“…Searching and stacking R genes with different resistance specificities has been a priority for rice breeders and pathologists worldwide (Hao et al, 2009). To date, over hundreds of major and minor rice blast R genes have been identified, 19 of which (including Pi-d2) have been cloned (Ballini et al, 2008;Sharma et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Searching and stacking R genes with different resistance specificities has been a priority for rice breeders and pathologists worldwide (Hao et al, 2009). To date, over hundreds of major and minor rice blast R genes have been identified, 19 of which (including Pi-d2) have been cloned (Ballini et al, 2008;Sharma et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this research, to identify polymorphism in Sri Lankan rice germplasm, simple sequence repeats markers (RM206, RM246) and gene marker (YL87/YL155) were incorporated based on a genealogy study that was conducted on the highly blast resistant variety Tetep by us prior to this study. It identified several IR varieties such as IR64, IR24, IR8, IR36 and mainly a Vietnamese variety Tetep (Sharma et al, 2012) contributed blast resistant genes to Sri Lankan germplasm. The markers RM206, RM246 and YL87/YL155 are linked to the blast resistant genes, Pita, Pit (p) and Pikh respectively in variety Tetep (McCouch et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The identification and isolation of additional host R-genes and pathogen avirulence genes is important to understand the molecular mechanisms involved in the hostÁpathogen interaction. So far, about 100 major rice blast resistance genes have been identified, and few of them have been characterized (Sharma et al 2012). All the cloned R-genes have been classified into five groups based on their predicted protein structure (Hammond-Kosack & Jones 1997).…”
Section: Introductionmentioning
confidence: 99%
“…From the present study, it can be concluded that the LRR domain is more diversified as compared to the NB-ARC domain. Most isolated R genes encode proteins possessing a LRR domain, of which the majority also contains a NBS domain (Sharma et al 2012). Two basic strategies have evolved for an R protein to recognize a pathogen effector (which is also called avirulence [Avr] factor): direct physical interaction and indirect interaction via association with other host proteins targeted by the Avr factor.…”
mentioning
confidence: 99%